Analysis of Speech Acts in The Animation Serial Film Upin & Ipin and Adit Sopo & Jarwo - Moh Kavin Lidinillah (Institut Agama Islam Tarbiyatut Tholabah, 2023)
This research aims to describe the forms of speech acts in theform of non-speech locution, illocution, and perlocution in theanimated films of Adit Sopo and Jarwo and Upin & Ipin. Themethod used in this research is descriptive qualitative method.The sources obtained were through the animated films of AditSopo and Jarwo and Upin & Ipin on episodes with the themeof Eid. Based on data analysis, it has been found that in theanimated film Adit Sopo and Jarwo there are types of speechacts of locution, illocution, and perlocution. Likewise with theanimated film Upin and Ipin. In the animated film Adit Sopo& Jarwo, speech acts that often appear are illocutionary acts ofdirective type, and the least that appears is the act of speechmanagement, as well as Upin & Ipin animated films. Thisshows that the location of neighboring countries and culturesthat are not so much different in celebrating Eid can beinfluential in making the two animated films so that the speechacts that appear have almost the same percentage.